Transcriptomic responses to aluminum (Al) stress in maize - Li-ming XU; Chan LIU; Bao-ming CUI; Ning WANG; Zhuo ZHAO; Li-na ZHOU; Kai-feng HUANG; Jian-zhou DING; Han-mei DU; Wei JIANG; Su-zhi ZHANG (Journal of Integrative Agriculture, 2018)
Aluminum (Al) toxicity is a major factor limiting crop production and plant growth in acid soils. The complex inheritance of Al toxicity and tolerance mechanisms in maize has uncharacterized yet. In this study, the maize inbred line 178 seedlings were treated with 200 µmol L–1 CaCl2+0 µmol L–1 AlCl3 (control) and 200 µmol L–1 CaCl2+60 µmol L–1 AlCl3 (Al treatment) for 1 and 6 h, respectively. The experiment was repeated three times. Then a detailed temporal analysis of root gene expression was performed using an Agilent GeneChip with 34 715 genes, only the genes showing more than 2.0-fold difference (P<0.01) between the control and the Al treatment maize seedlings were analyzed further. Thus, a total of 832 different expression genes, 689 significantly up-regulated and 143 down-regulated, were identified after the seedlings were treated with Al for 6 h. And 60 genes, 59 up-regulated and one down-regulated, were also detected after the seedlings were treated for 1 h. Replicated transcriptome analyses further showed that about 61% of total significantly genes could be annotated based on plant genome resources. Quantitative real-time PCR (qRT-PCT) of some selected candidate genes was used to demonstrate the microarray data, indicating significant differences between the control and Al-treated seedlings. Exposure to Al for 6 h triggered changes in the transcript levels for several genes, which were primarily related to cell wall structure and metabolism, oxidative stress response, membrane transporters, organic acid metabolism, signaling and hormones, and transcription factors, etc. After Al-treated for 1 h, differential abundance of transcripts for several transporters, kinase, and transcription factors were specifically induced. In this study, the diversity of the putative functions of these genes indicates that Al stress for a short stage induced a complex transcriptome changes in maize. These results would further help us to understand rapid and early mechanisms of Al toxicity and tolerance in maize regulated at the transcriptional level.